2020
DOI: 10.3390/ma13235486
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Durability of Recycled Masonry Aggregate Concrete

Abstract: The use of recycled masonry aggregate for concrete is mostly limited by the worse properties in comparison with natural aggregate. For these reasons it is necessary to find ways to improve the quality of recycled masonry aggregate concrete and make it more durable. One possibility is utilization of crystalline admixture which was verified in this study by laboratory measurements of key material properties and durability. The positive influence of mineral admixture was proved for freeze-thaw resistance. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Since clay brick is a kind of low-strength porous material, mixing it into RA and using it as a recycled raw material will further reduce the density and strength and increase the crushing index [ 12 ]. Discarded clay brick also leads to a high water absorption coefficient and affects the water–cement ratio (W/C) of concrete [ 30 , 31 , 32 ]. To avoid the absorption of RA to mixing water, Pacheco-Torgal and Anderson et al soaked RA for 24 h then transformed it into a saturated dry surface state [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since clay brick is a kind of low-strength porous material, mixing it into RA and using it as a recycled raw material will further reduce the density and strength and increase the crushing index [ 12 ]. Discarded clay brick also leads to a high water absorption coefficient and affects the water–cement ratio (W/C) of concrete [ 30 , 31 , 32 ]. To avoid the absorption of RA to mixing water, Pacheco-Torgal and Anderson et al soaked RA for 24 h then transformed it into a saturated dry surface state [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, fRCAC mixtures prepared by the Czech team achieved more favorable results in carbonation resistance, where increase in carbonation depth was observed in one mixture (fRCAC1 IA) only. However, from the point of view of previous studies carried out by the same research group [91,92], the negative influence of fRA is significantly lower than the impact of coarse RA.…”
Section: Carbonation Resistancementioning
confidence: 80%
“…Water flow in the system is natural under gravity or capillarization method [90]. A 250-room hotel in Birmingham, UK, with the rainwater recycling system saved up to 780 m 3 of potable water per year [91]. According a comparative simulation model, gravity fed rainwater harvesting system for a high rise building in Mexico saved up to 8.5% of GHG [92].…”
Section: Alternate Water Resources For Water Reusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tam et al [12] used three acid solutions to remove the mortar from the RCA surface, effectively reducing the water absorption of the RCA while leaving the alkalinity of the aggregate unaffected. Pavlu et al [13,14] showed that crystal admixtures could fill the pores in recycled masonry aggregate, thereby improving the mechanical properties and durability of recycled masonry concrete. Spaeth et al [15] used a polymer impregnation treatment to significantly reduce the water absorption of RCA and improve its resistance to cracking.…”
Section: Introductionmentioning
confidence: 99%